Socio-Cultural Mobility as a Condition for Professional Activation of Staff - Shpektorenko, Igor Valentinovich; Lysenko Olena Oleksiivna (European Journal of Multidisciplinary Studies, 2020)
We have identified the basic types of human mobility: social, professional, academic and some mixed types: socio-professional, professional-academic, socio-cultural, etc. Carryed out a comparative, comprehensive analysis, applying the method of sequential comparison of different interpretations of the concept of "socio-cultural mobility" with the use of systematic analysis, we substantiated the basic meaning of this concept: quality inherent in human (individual) which indicate a high level of social and cultural competence, social and general culture of the individual; the process of individual and group mobility of people in different socio-cultural environments (including professional environments in which a person operates), the process of realization of personal qualities, especially those that determine their ability to master social and cultural values and norms of a particular environment; achieved (or determined) result of activity, mobility in different socio-cultural environments (realized the potential of this type of human mobility for a certain period); criterion for evaluating activities in different socio-cultural environments, effectiveness, productivity, efficiency of the specified socio-cultural activities of man.
Keywords: socio-cultural mobility, condition, professional, activation, staff